Phylogeography of the widespread Caribbean spiny orb weaver Gasteracantha cancriformis (2020)
Background: Modern molecular analyses are often inconsistent with pre-cladistic taxonomic hypotheses, frequently indicating higher richness than morphological taxonomy estimates. Among Caribbean spiders, widespread species are relatively few compared to the prevalence of single island endemics. The taxonomic hypothesis Gasteracantha cancriformis circumscribes a species with profuse variation in size, color and body form. Distributed throughout the Neotropics, G. cancriformis is the only morphological species of Gasteracantha in the New World in this globally distributed genus.Methods: We inferred phylogenetic relationships across Neotropical populations of Gasteracantha using three target genes. Within the Caribbean, we estimated genetic diversity, population structure, and gene flow among island populations.Results: Our findings revealed a single widespread species of Gasteracantha throughout the Caribbean, G. cancriformis, while suggesting two recently divergent mainland populations that may represent separate species, diverging IMages, or geographically isolated demes. The concatenated and COI (Cytochrome c oxidase subunit 1) phylogeny supported a Caribbean Glade nested within the New World. Genetic variability was high between island populations for our COI dataset; however, gene flow was also high, especially between large, adjacent islands. We found structured genetic and morphological variation within G. cancriformis island populations; however, this variation does not reflect genealogical relationships. Rather, isolation by distance and local morphological adaptation may explain the observed variation.